The Influence of Online Learning, The Role of Parents, and Learning Motivation on The Learning Outcomes of Physical Education and Sports - Triyadi Santoso; Ramdan Pelana; Taufik Rihartno; Rizka Antoni (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The purpose of this study is to find out the influence of online learning, the role of parents, and learning motivation on the learning outcomes of physical education and sports of Outstanding School Students 02 Jakarta era covid-19 pandemic . This type of research is qualitative research with a causal associative correlation approach. The number of study subjects was 49 respondents. These research steps include; 1) the stage of data collection; 2) data analysis and 3) the testing phase of data analysis. Furthermore, data analysis testing is conducted through: 1) normality test; 2) test homogeneity; 3) Test the linearity and significance of the regence equation. The conclusion of this study there is a significant influence between online learning, the role of parents, learning motivation and physical education learning outcomes of Outstanding School 2 Jakarta students in the Covid-19 pandemic era.